2005
DOI: 10.1354/vp.42-6-805
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant p53 Expression in Feline Vaccine-associated Sarcomas and Correlation with Prognosis

Abstract: Abstract. Eighty spontaneously occurring feline vaccine-associated sarcomas (VAS) were evaluated to determine the immunohistochemical expression of the tumor suppressor gene p53. Sixty-five of 80 VAS (81%) exhibited positive immunoreactivity with Mab240, a murine monoclonal antibody that specifically recognizes mutated p53. Only 44 of 81 tumors (55%) were positive with rabbit polyclonal antibody CM-1. CM-1 often yielded nonspecific staining of nonneoplastic tissues. Nonspecific staining was greatly reduced or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
0
7

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 35 publications
0
35
0
7
Order By: Relevance
“…Nuclear accumulation of p53 protein is an indication of mutation in the p53 gene [21,22]. As an initial screen for possible p53 mutants, we used immunocytochemistry to detect abnormal expression of p53 in four canine OS cell lines.…”
Section: Methodsmentioning
confidence: 99%
“…Nuclear accumulation of p53 protein is an indication of mutation in the p53 gene [21,22]. As an initial screen for possible p53 mutants, we used immunocytochemistry to detect abnormal expression of p53 in four canine OS cell lines.…”
Section: Methodsmentioning
confidence: 99%
“…5 In general, histologic subtype often correlates with biological behavior; however, in the case of ISSs, the prognostic value of histogenetic classification is questionable. [6][7][8][9] Analysis of prognostic factors associated with injection-site sarcomas in cats: 57 cases (2001)(2002)(2003)(2004)(2005)(2006)(2007) Abbreviations ISS Injection-site sarcoma STS Soft tissue sarcoma Nevertheless, some authors have tried to identify low-and high-risk groups as well as factors associated with survival, metastatic spread, and local tumor recurrence.…”
mentioning
confidence: 99%
“…An analysis of prognosis for 61 cats treated by surgery alone was retrospectively provided in a study. 8 The aim of the study reported here was to retrospectively evaluate whether factors such as sex, age, anatomic site of tumor, tumor size, histologic grade, excision of primary tumors or excision of recurrent ISSs, use of excision alone or excision plus adjuvant therapy, and development of local recurrent ISSs or distant metastasis were prognostic factors of survival time in cats with ISSs. In 2 further studies, 9,14 the only significant factor found to be related to disease-free interval was completeness of excision.…”
mentioning
confidence: 99%
“…2,23,27 Mutations in the p53 gene have been identified 28 and immunohistochemical expression of p53 is also abnormal in FISSs. 29,30 R E V I E W / Musculoskeletal neoplasia in the cat …”
Section: Pathogenesis and Pathologymentioning
confidence: 99%